The Capital Gains and Losses on U.S. Government Debt: 1942-1987 - Cox, W. Michael; Lown, Cara S. (The Review of Economics and Statistics, 1989)
The capital gains and losses on U.S. Treasury securities are calculated and reported on a quarterly basis over the 1942-87 period. These data are then used to calculate an adjusted measure of the federal budget deficit for the years 1975-87. Whereas the rising trend in interest rates over the 1975-81 period substantially reduced the federal deficit, this study shows that the reversal of that trend over the 1981-86 period contributed even more greatly to an increase in the deficit. Also calculated and reported are holding-period rates of return on overall marketable Treasury debt, providing a contrast to existing interest rate series. Copyright 1989 by MIT Press.